2014
DOI: 10.1001/jamadermatol.2013.8442
|View full text |Cite
|
Sign up to set email alerts
|

Dark Homogeneous Streak Dermoscopic Pattern Correlating With SpecificKITMutations in Melanoma

Abstract: While future study is required, these results have multiple implications. (1) The underlying melanoma-driving mutations may give rise to specific dermoscopic growth patterns, (2) BRAF/NRAS mutations in early melanomas may not be as common as previously thought, and (3) patients may be predisposed to developing specific driving mutations giving rise to melanomas or nevi of similar growth patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…This feature is usually detected in lesions typified by a fast growing attitude such as Spitz/Reed naevi and melanomas. In the latter, a recent study has proven that peripheral streaks are also linked to a specific c-KIT mutation [11]. Our results confirmed that peripheral streaks in thin melanomas are a dermoscopic feature related to tumour aggressiveness [12] since the presence of mitoses is a direct sign of tumour proliferation.…”
Section: Discussionsupporting
confidence: 86%
“…This feature is usually detected in lesions typified by a fast growing attitude such as Spitz/Reed naevi and melanomas. In the latter, a recent study has proven that peripheral streaks are also linked to a specific c-KIT mutation [11]. Our results confirmed that peripheral streaks in thin melanomas are a dermoscopic feature related to tumour aggressiveness [12] since the presence of mitoses is a direct sign of tumour proliferation.…”
Section: Discussionsupporting
confidence: 86%
“…Instead, melanomas with a dermoscopically dark homogeneous streak pattern have been recently linked to a specific KIT mutation (37). This finding is consistent with a previous report showing that KIT was mutated/overexpressed in darkly pigmented cutaneous melanomas (38).…”
Section: Tschandl Et Al Investigated the Frequency Of Braf Mutationssupporting
confidence: 88%
“…In other words, the more a given tumour manifests the presence of streaks, the more it tends to grow. A previous study reported that the dermoscopic presence of dark homogeneous streaks pattern had unique KIT mutations in the second catalytic domain of KIT in exon 17 for all three samples tested. Although KIT mutations have not been explored in our data set, our results indicate that streaks represent a candidate dermoscopic substrate of specific underlying melanoma‐driven mutations.…”
Section: Discussionmentioning
confidence: 73%